(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2026)
This study investigates Saudi EFL learners’ perceptions of AI-assisted translanguaging as a pedagogical strategy in English Medium Instruction (EMI) classrooms. Drawing on a structured Likert-scale questionnaire administered to 122 undergraduate EFL students, the research explores how AI tools mediate comprehension, reduce anxiety, and enhance participation in EMI contexts. Descriptive statistical analysis revealed that learners generally held positive attitudes toward AI-mediated translanguaging, with high levels of agreement regarding its role in improving comprehension, confidence, vocabulary retention, and active engagement with course materials. While students acknowledged challenges such as continued dependence on teachers and difficulties in processing fast-paced English input, they also emphasized the motivational benefits of AI tools in extending learning beyond classroom boundaries. The findings underscore the pedagogical potential of AI-assisted translanguaging for creating inclusive, supportive, and effective EMI environments, offering implications for curriculum design, teacher training, and policy development in Saudi higher education.